Komunikasi Terapeutik dalam Novel Tapak Sabda Melalui Dakwah Bil Kitabah - Anton Widodo (IAIN Padangsidimpuan, 2020)
Basically the pattern of da'wah is not much different from the communication pattern that is da'i - message - uslub - media - mad'u. Da'wah through true writing can provide flexibility to the preacher, to convey the message of preaching in detail. The type of research conducted was qualitative. Qualitative research is the process of finding data images from the context of events directly in an effort to paint events that are exactly the same as reality, which makes various events such as glue and involving participative perspectives in various events, and uses induction in explaining the picture of the phenomenon being observed. The results of this study are concluded that therapeutic communication in the Word Tread Word conveys the message of the chanting through what is implied in the novel, such as preaching messages about Islamic Philosophy written in the form of letters sent by the